Effectiveness of virtual laboratories in terms of learning environment, attitude and achievement among high-school genetics students - Oser, R.; Fraser, Barry (James Nicholas Publishers, 2015)
As society becomes increasingly global and experiential, research suggests that students can benefit from alternative learning environments that extend beyond the classroom. In providing students with laboratory experiences that otherwise would not be possible in high-school settings, virtual laboratories can simulate real laboratories and encourage students to employ scientific thinking skills. We investigated the effectiveness of some virtual laboratories in terms of students’ perceptions of the learning environment, attitudes towards science and achievement. For a sample of 322 grade 8-10 students in 12 classes in the USA, students who utilised virtual laboratories were compared with students who did not. Our finding of no significant differences between instructional groups suggests that the promise of using these technological interventions in school classrooms might not be fulfilled, but also suggests that virtual laboratories can be used as alternative or supplementary methods without negatively affecting students. Although virtual laboratories were not effective overall for all students, significant instruction-by-sex interactions suggested that virtual laboratories were advantageous for males but disadvantageous for females on several criteria.